1968
DOI: 10.1128/aem.16.7.1002-1005.1968
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Protein Feed Supplements Produced by Rendering Plants1

Abstract: Samples of protein feed supplements produced by rendering plants were examined for salmionellae, total aerobic bacterial counts, coliform counts, and enterococci. Isolations of salmonellae were more frequent from products with high counts; however, 6% of the samples with total counts of less than 1,000 per gram and 14% of the samples with coliform counts of less than 1 per gram contained salmonellae. Serotypes of Escherichia coli which have been associated with disease in domestic animals and poultry were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1968
1968
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The predominant microbial species in animal feed may also vary between different feed types and processing conditions. Loken et al 7 reported that Micrococcus and Bacillus predominate in protein feed supplements, while Cox et al 2 isolated Eterobacteriacae such as Enterobacter agglomerans, Ent cloacae and Klebsiella pneumoniae from commercial poultry diets. In a series of studies, Ha et al 4, 6, 8–10 detected aerobic populations ranging between 10 4 and 10 7 CFU g −1 in a soybean meal‐based poultry mash, and an average population of 10 5 CFU g −1 in feed containing meat and bone meal.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant microbial species in animal feed may also vary between different feed types and processing conditions. Loken et al 7 reported that Micrococcus and Bacillus predominate in protein feed supplements, while Cox et al 2 isolated Eterobacteriacae such as Enterobacter agglomerans, Ent cloacae and Klebsiella pneumoniae from commercial poultry diets. In a series of studies, Ha et al 4, 6, 8–10 detected aerobic populations ranging between 10 4 and 10 7 CFU g −1 in a soybean meal‐based poultry mash, and an average population of 10 5 CFU g −1 in feed containing meat and bone meal.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of salmonellae in feed and feed components has frequently been associated with the use of contaminated animal protein supplements processed by rendering plants (1,(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%